Mediacje w praktyce wojewódzkich sądów administracyjnych – urzeczywistnienie idei demokratycznego państwa prawa - Wartenberg-Kempka, Barbara; Zacharko, Lidia (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
Provisions on mediation in administrative court proceedings were introduced to the Polish legal system with effect from 1 January 2004. Despite the passage of more than twelve years since its introduction, the institution of mediation is used to a small extent. In literature, there are implications for the institution of mediation to be in conflict with the essence of administrative justice. On the other hand, it is stressed that Poland as a European Union member state is obliged to ensure the availability of mediation services. In this situation, consideration should be given whether or not there is a need to improve and adapt the existing legislation to the current needs, taking into account the experience gained during its operation, so that it becomes the basis for the increased use of the mediation institution.
Keywords: the democratic rule of law; judicial administration; mediation